2019
DOI: 10.31234/osf.io/5skrd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Looking for the Right Swipe: Gender Differences in Self-Presentation on Tinder Profiles

Abstract: Tinder has become a popular online dating tool for people looking for either short- or long-term relationships. In this study we build on existing research on gender differences in the motivations of Tinder users, by analyzing gender differences in self-presentation. We predicted that women would try to attract men to right-swipe (i.e., potentially match) their profiles through largely visual means; while men would put more emphasis on showing off their skills and interests. In a sample of 300 randomly obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…They also reported that girls were consistently more likely to engage in other-oriented social media use across all time points. Several other authors have also reported that there are gender differences in relation to self-presentation on social media [ 18 , 26 , 27 ]. Herring and Kapidzic reported for instance that adolescent girls are more likely to present their friendship ties on social media, while boys post updates more related to technology, sports, and humor [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that girls were consistently more likely to engage in other-oriented social media use across all time points. Several other authors have also reported that there are gender differences in relation to self-presentation on social media [ 18 , 26 , 27 ]. Herring and Kapidzic reported for instance that adolescent girls are more likely to present their friendship ties on social media, while boys post updates more related to technology, sports, and humor [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the relationship between the two parties gradually warms up, the connection on the unfamiliar social platform is usually transferred to other acquaintance social platforms and software [6]. For example, after two users have the intention of further communication.…”
Section: Relationship Transfermentioning
confidence: 99%
“…Aunque puede ser definido como una muestra de libertad de expresión sexual (Mercado Contreras et al, 2016), medio de mantenimiento y fortalecimiento de las relaciones sentimentales (Ingram et al, 2019) o proceso de formación de identidad tecnológica, (Soriano Ayala et al, 2019) por las características propias de la práctica se le considera más un riesgo que una oportunidad. Valdivieso López et al ( 2017) explican que «El sexting representa una pérdida de la privacidad con respecto a la intimidad de las personas, exponiendo a las personas a la crítica pública, así como a posibles extorsiones y problemas familiares» (párr.…”
Section: Sextingunclassified